Assessment of the dissipation, pre‐harvest interval and dietary risk of carbosulfan, dimethoate, and their relevant metabolites in greenhouse cucumber (Cucumis sativus L.). Issue 7 (23rd March 2018) - Geng, Yue; Jiang, Linjie; Zhang, Yanwei; He, Zeying; Wang, Lu; Peng, Yi; Wang, Yuehua; Liu, Xiaowei; Xu, Yaping
Abstract: BACKGROUND: The dissipation behavior, pre‐harvest interval and dietary risk of carbosulfan, dimethoate, and their relevant metabolites were investigated in greenhouse cucumber in Tianjin, northern China, to ensure raw consumption safety. RESULTS: Carbosulfan was metabolized to carbofuran, dibutylamine, 3‐hydroxycarbofuran and 3‐ketocarbofuran, and dimethoate was degraded to omethoate in cucumber fruits and leaves. The dissipation of carbosulfan, carbofuran, 3‐hydroxycarbofuran and dimethoate fitted first‐order kinetics well, with R 2 ranging from 0.912 to 0.992, and their half‐lives were 2.6, 2.7, 2.4 and 5.2 days in cucumber fruits and 2.8, 3.0, 4.6 and 2.5 days in leaves, respectively. The estimated daily intakes of the active ingredients and their relevant metabolites were 0.1–4% of the corresponding acceptable daily intakes. Acute oral exposure to carbofuran (a metabolite of carbosulfan) represented 367% of the acute reference dose (ARfD) for 1–6‐year‐old Chinese children and 227% for the general Chinese population. CONCLUSION: A minimum pre‐harvest interval of 12 days for carbosulfan is proposed to ensure safe consumption of cucumber. The slow dissipation rate of omethoate in cucumber reveals that a longer pre‐harvest interval (≥ 27 days) is necessary to prevent dietary risk when dimethoate is applied to cucumber. © 2018 Society of Chemical Industry Abstract : Dissipation and dietary risk of carbosulfan, dimethoate, and their relevant metabolites were investigated in greenhouse cucumber. Suitable pre‐harvest intervals for both insecticides are proposed for safe consumption of raw cucumber.